1991
DOI: 10.1111/j.1365-2222.1991.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between IgG1 and IgG4 antibodies to foods and the development of IgE antibodies to inhalant allergens. I. Establishment of a scoring system for the overall food responsiveness and its application to 213 unselected children

Abstract: To obtain reference levels for subsequent investigations, we analysed the IgG1 and IgG4 antibody levels to common foods in the sera of 213 unselected children (age 3 months to 14 years). The children were clustered into five age groups and tested on a broad screening panel of common foods. We used the IgG1 and IgG4 RAST with Sepharose-coupled antigens: cows' milk, hens' egg white, banana, legumes (a mixture of soybean and peanut), grains (a mixture of wheat and rice), potato, orange and pork. In all age groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…I n a previous paper [ 14], we established an age-and (to some extent) diet-independent scoring system for IgGi and IgG.] responsiveness to foods.…”
Section: Discussionmentioning
confidence: 99%
“…I n a previous paper [ 14], we established an age-and (to some extent) diet-independent scoring system for IgGi and IgG.] responsiveness to foods.…”
Section: Discussionmentioning
confidence: 99%
“…The foods tested were cow’s milk, chicken’s egg white, orange, meat, potato, a mixture of wheat and rice and a mixture of soybean and peanut. These foods were selected in an earlier study [ 21]. The selected antigens cover the normal spectrum of foods given to infants in The Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…During an investigation of the antibody response to a broad panel of ingested foods [2,3], we found that the IgG antibody response to banana extract was much stronger than expected on the basis of quantities commonly in gested. This was particularly the case for lgG4 antibodies and much less so for IgGl or IgA antibodies.…”
Section: Introductionmentioning
confidence: 99%